Innovative solutions of folk music in tradition renovation - Dukaļska, Iveta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
In the cultural historical experience of humankind the traditions inherited from a generation to a generation form substantial basis for development of any society. With social changes, changes in the lifestyle of a community along with changes in the concept of values, culture develops, based on the model of basic values and innovation. Folk music-making tradition is among the components characterising the culture of a given society, possessing certain specifics: most frequently it means lack of the formal musical training and inability to read notation, meaning that the music is played by ear, the age of musicians, use of folk instruments, situations of performance and repertoire. The article discusses the types of innovation and their influence on the tradition of folk-music-making, also analysing the opportunities for the restoration of the tradition in in the cultural space of the 21st century.